'Efficacy of sodium alginate, xanthan gum, and diatomite admixtures in improving the strength and shrinkage behaviour of EPS lightweight concrete'. Issue 5 (4th April 2023) - Alselwi, Othman; Li, Bi Xiong; Liu Yue, Su; Zhi wen, Wang
Abstract: The aim of this study is to demonstrate the effectiveness of cement admixtures in improving the shrinkage and strength resistance of EPS lightweight concretes (ELCs). A group of EPS mixtures containing 0.5, 1 and 2% of sodium alginate, 0.1, 0.3 and 0.5% of xanthan gum and 2, 5 and 8% of diatomite was used. The results of the study showed that increasing the dose of each admixture significantly improved the strength and shrinkage resistance of ELC. Although the application of sodium alginate, xanthan gum and diatomite as cement admixtures decreased the water loss ratio of EPS concrete compared to the reference mix, the increase in their contents increased the water loss ratio of EPS concrete. The increase in sodium alginate, xanthan gum and diatomite content improved the EPS concrete pore structure stability and performance of the interface of transition zones (ITZ) between the cement slurries and EPS aggregates, which had a positive role in improving the strength and shrinkage behaviour of ELC. Application of 2% sodium alginate, 0.5% of xanthan gum and 8% of diatomite can be recommended as the preferred dose of cement admixtures to improve the strength and shrinkage performance of ELC.